RI 8733 Recovery of Sulfur and Accessory Metals From a Leaching Process Residue - K. P. V. Lei (The National Institute for Occupational Safety and Health (NIOSH), 1982)
The Bureau of Mines as part of its research effort to minimize the generation of hydrometallurgical waste, investigated a sodium sulfide leaching-electrolysis procedure for treating hydrometallurgical residues for elemental sulfur and base-metals recovery. Research was conducted on a leaching residue from a lead concentrate. The following procedure was developed. 1. The elemental sulfur was dissolved as polysulfide with an Na2S solution. 2. The resultant metal sulfide bearing residue was oxidatively acid leached in a cationic membrane electrolysis cell; the metals were solu¬bilized at the anode, and a base was generated at the cathode. 3. The elemental sulfur was recovered from the polysulfide solution by neutralizing with the acid in the anolyte. Byproducts of the neutralization were H2S and a sodium salt solution. 4. Sodium sulfide was regenerated by reacting the H2S byproduct with the base in the catholyte. 5. Lead as PbCL2 was recovered from the anode residue by brine leaching, and the other metals were recovered from the sodium salt solution as metal sulfides. 6. The barren filtrate from the metal sulfide precipitation constituted the recycled electrolyte. Ninety-eight percent of the elemental sulfur, 98 pct of the lead, and up to 80 pct of other accessory metals were recovered from a residue obtained from the FeCl3-NaCl leaching of a lead concentrate.